Learning English Slang Through Social Media: Impact on Learners’ Identity and Confidence - Milda Siti Fauziyah; Haura Najwa Zahara Nilufar; Risma Naimah Abdurahman; Ummi Kultsum (Universitas Islam Negeri Palopo, 2025)
For Indonesian EFL students, social media has emerged as a significant source of English exposure, particularly for colloquial language like slang. However, little is known about the kinds of slang that students really pick up and how this affects their confidence and sense of self. This study is to investigate (1) the kinds of English slang that are frequently acquired through social media, (2) how learners' identities are shaped by this exposure, and (3) how it impacts their confidence in speaking the language. Seven ninth-grade students were interviewed and questionnaires were used to gather data using a qualitative descriptive design. According to the findings, learners most commonly pick up brief, repetitive slang, such as acronyms (like LOL and OMG) and hybrid forms of Indonesian and English that are disseminated by influencers. Despite the fact that students frequently come with these terms online, their usage is still restricted and primarily receptive. Exposure to slang somewhat enhances understanding and self-expression, but confidence varies according to social context.